THE ROLE OF MECHANOACTIVATION OF CARBON BLACK NANOPARTICLES IN THE FORMATION OF SEGREGATED STRUCTURE AND PROPERTIES OF POLYMERIC CONDUCTIVE NANOCOMPOSITES - Allahverdiyeva, Khayala V.; Kakhramanov, Najaf T.; Hasanova, Aynura A.; Koseva, Nely S. (ChemChemTech, 2025)
The study of the influence of mechanical activation of nanoparticles on the structure and properties of polymer composites has received very little attention in the literature. In some cases, this circumstance leads to the receipt of contradictory information. Therefore, in this paper, the effect of mechanical activation of Printex XE 2B carbon black nanoparticles on the tensile strength, elongation at break and electrical conductivity of polyolefin-based nanocomposites is considered. The polyolefins used were high-density polyethylene, low-density polyethylene, ethylene-hexene copolymer, ethylene-butene copolymer, isotactic polypropylene, statistical random polypropylene copolymer, and ethylene-propylene block copolymer. It has been shown that as a result of mechanical activation of carbon black nanoparticles in a centrifugal mill, a decrease in bulk density by almost 12 times is observed. A number of assumptions are given to explain the very fact of a decrease in bulk density. Data on properties before and after mechanical activation are provided. It has been shown that mechanical activation has different effects on the nature of changes in electrical conductivity. It has been established that the higher the crystallinity of the initial polymer matrix, the more pronounced the segregation effect is, and at a lower concentration of carbon black, high values of chain conductivity are observed in the interphase region. At the same time, mechanical activation in the presence of a compatibilizer contributes to some increase in the tensile strength and elongation at break of nanocomposites. The hypothesis that as a result of mechanical activation of nanoparticles, the latter become electrified is considered. It is assumed that during the grinding of mineral materials, the growth of newly formed surfaces occurs, which have a high energy potential, capable of improving the interaction at the polymer-filler phase boundary. For citation: Allahverdiyeva Kh.V., Kakhramanov N.T., Hasanova A.A., Koseva N.S. The role of mechanoactivation of carbon black nanoparticles in the formation of segregated structure and properties of polymeric conductive nanocomposites. ChemChemTech [Izv. Vyssh. Uchebn. Zaved. Khim. Khim. Tekhnol.]. 2025. V. 68. N 6. P. 126-133. DOI: 10.6060/ivkkt.20256806.7190.